Understanding the workplace: a research framework for industrial archaeology in Britain: 2005 - Gwyn, David, author.
1 online resource (200 pages)
Keywords: "This volume was first delivered at a conference organised by the Association for Industrial Archaeology in Nottingham in June 2004, and formerly constituted a special issue of Industrial Archaeology Review. The papers have the explicit intention of formulating a research framework for industrial archaeology in the 21st century and demonstrating how far industrial archaeology is now a fully recognised element of mainstream archaeology."